The comparison of public service advertising style between Malaysian and Singapore : a preliminary research - Julia Tan Yin Yin; Yohan Kurniawan; Siti Bahirah Saidi (2013)
Advertisement is one important tool in the process of selling a product or recruitment process. Civil service is one of the sectors that need to use advertisement to get the attention of the public. This research aimed to compare the form of a poster advertisement for the recruitment of police personnel between Malaysia and Singapore. This study used observation technique for collecting data. Data were gathered at LRT station, Kuala Lumpur (Malaysia) and MRT stations, Singapore; where posters were analyzed to compare to advertising and motivation theory. Result shows that the Singapore Police recruitment advertising has a clearer and better message than Malaysia’s. This is due to urgent needs of police personnel and also because it is extremely tough to attract people to join the police force in Singapore. Therefore, the Singapore Police produced advertisements that interest teenagers and young people to participate in the Singapore Police Force.